GE_GERICHTE C/12057/2014 vom 3. Oktober 2017 - GE Cour de justice (2017)
VENTE D'IMMEUBLE ; PRIX D'ACHAT ; COMPENSATION DE CRÉANCES ; EXÉCUTION DE L'OBLIGATION ; DOMMAGE ; CLAUSE PÉNALE | CO.97; CO.120; CO.160; CO.169;